A hierarchical manifold microchannel heat sink array for high-heat-flux two-phase cooling of electronics. (February 2018) - Drummond, Kevin P.; Back, Doosan; Sinanis, Michael D.; Janes, David B.; Peroulis, Dimitrios; Weibel, Justin A.; Garimella, Suresh V.
Highlights: A hierarchical manifold microchannel heat sink is fabricated and tested in two-phase operation. A thin film, serpentine heater provides uniform heating over 5 mm × 5 mm area. An array of sensors monitors the device temperature field. Heat sinks with high-aspect-ratio microchannels are etched in silicon for intrachip cooling. Heat fluxes up to 910 W/cm 2 are dissipated using the dielectric fluid HFE-7100. Abstract: High-heat-flux removal is necessary for next-generation microelectronic systems to operate more reliably and efficiently. Extremely high heat removal rates are achieved in this work using a hierarchical manifold microchannel heat sink array. The microchannels are imbedded directly into the heated substrate to reduce the parasitic thermal resistances due to contact and conduction resistances. Discretizing the chip footprint area into multiple smaller heat sink elements with high-aspect-ratio microchannels ensures shortened effective fluid flow lengths. Phase change of high fluid mass fluxes can thus be accommodated in micron-scale channels while keeping pressure drops low compared to traditional, microchannel heat sinks. A thermal test vehicle, with all flow distribution components heterogeneously integrated, is fabricated to demonstrate this enhanced thermal and hydraulic performance. The 5 mm × 5 mm silicon chip area, with resistive heaters and local temperature sensors fabricated directly on the opposite face, is cooled by a 3 × 3 array of microchannel heat sinks that are fed with coolant using a hierarchical manifold distributor. Using the engineered dielectric liquid HFE-7100 as the working fluid, experimental results are presented for channel mass fluxes of 1300, 2100, and 2900 kg/m 2 s and channel cross sections with nominal widths of 15 μm and nominal depths of 35 μm, 150 μm, and 300 μm. Maximum heat flux dissipation is shown to increase with mass flux and channel depth and the heat sink with 15 μm × 300 μm channels is shown to dissipate base heat fluxes up to 910 W/cm 2 at pressure drops of less than 162 kPa and chip temperature rise under 47 °C relative to the fluid inlet temperature.